Adenosine-Metabolizing Enzymes, Adenosine Kinase and Adenosine Deaminase, in Cancer - Galina Zhulai; Eugenia Oleinik; Mikhail Shibaev; Kirill Ignatev (Biomolecules, 2022)
The immunosuppressive effect of adenosine in the microenvironment of a tumor is well established. Presently, researchers are developing approaches in immune therapy that target inhibition of adenosine or its signaling such as CD39 or CD73 inhibiting antibodies or adenosine A2A receptor antagonists. However, numerous enzymatic pathways that control ATP-adenosine balance, as well as understudied intracellular adenosine regulation, can prevent successful immunotherapy. This review contains the latest data on two adenosine-lowering enzymes: adenosine kinase (ADK) and adenosine deaminase (ADA). ADK deletes adenosine by its phosphorylation into 5′-adenosine monophosphate. Recent studies have revealed an association between a long nuclear ADK isoform and an increase in global DNA methylation, which explains epigenetic receptor-independent role of adenosine. ADA regulates the level of adenosine by converting it to inosine. The changes in the activity of ADA are detected in patients with various cancer types. The article focuses on the biological significance of these enzymes and their roles in the development of cancer. Perspectives of future studies on these enzymes in therapy for cancer are discussed.